Variation in vasopressin receptor Avpr1a) expression creates diversity in behaviors related to monogamy in prairie voles - Barrett, Catherine E. (2013)
Polymorphisms in noncoding regions of the vasopressin 1a receptor gene (Avpr1a) are associated with a variety of socioemotional characteristics in humans, chimpanzees, and voles, and may impact behavior through site-specific variation in gene expression. The socially monogamous prairie vole offers a unique opportunity to study such neurobiological control of individual differences in complex behavior. Vasopressin 1a receptor (V1aR) signaling is necessary for the formation of the pair bond in males, and prairie voles exhibit greater V1aR binding in the reward-processing ventral pallidum than do asocial voles of the same genus. Diversity in social behavior within prairie voles has been correlated to natural variation in neuropeptide receptor expression in specific brain regions. Here we use RNA interference to examine the causal relationship between intraspecific variation in V1aR and behavioral outcomes, by approximating the degree of naturalistic variation in V1aR expression. Juvenile male prairie voles were injected with viral vectors expressing shRNA sequences targeting Avpr1a mRNA into the ventral pallidum. Down-regulation of pallidal V1aR density resulted in a significant impairment in the preference for a mated female partner and a reduction in anxiety-like behavior in adulthood. No effect on alloparenting was detected. These data demonstrate that within-species naturalistic-like variation in V1aR expression has a profound effect on individual differences in social attachment and emotionality. RNA interference may prove a useful technique to unite the fields of behavioral ecology and neurogenetics to perform ethologically relevant studies of the control of individual variation and offer insight into the evolutionary mechanisms leading to behavioral diversity.